Technique of Biportal Endoscopic Transforaminal Lumbar Interbody Fusion - Heo, Dong Hwa; Hong, Young Ho; Lee, Dong Chan; Chung, Hun Jae; Park, Choon Keun (Neurospine, 2020)
Biportal endoscopic transforaminal lumbar interbody fusion (TLIF) may have advantages of minimally invasive fusion surgery as well as those of endoscopic surgery. The purpose of this study was to present the biportal endoscopic TLIF technique along with video presentations and a review of the literature on this technique. Basically, the biportal endoscopic TLIF technique is similar to minimally invasive TLIF with a tubular retractor. There were 2 options in the biportal endoscopic TLIF procedures. The first was the insertion of one long TLIF cage and the other was the insertion of 2 short posterior lumbar interbody fusion (PLIF) cages. After the interbody fusion procedures, percutaneous pedicles screw fixation was performed. Biportal endoscopic TLIF achieved complete neural decompression through laminectomy and facetectomy like conventional TLIF. Endplate preparation was performed completely under a clear and magnified endoscopic view. It was also feasible to insert a large TLIF cage or 2 cages for PLIF without exiting nerve root injury. Biportal endoscopic TLIF might have the advantages of endoscopic surgery as well as minimally invasive fusion surgery. Direct neural decompression, endplate preparation under endoscopic guidance, and the insertion of a large TLIF cage or 2 PLIF cages may be the merits of biportal endoscopic lumbar fusion procedures.Biportal endoscopic transforaminal lumbar interbody fusion (TLIF) may have advantages of minimally invasive fusion surgery as well as those of endoscopic surgery. The purpose of this study was to present the biportal endoscopic TLIF technique along with video presentations and a review of the literature on this technique. Basically, the biportal endoscopic TLIF technique is similar to minimally invasive TLIF with a tubular retractor. There were 2 options in the biportal endoscopic TLIF procedures. The first was the insertion of one long TLIF cage and the other was the insertion of 2 short posterior lumbar interbody fusion (PLIF) cages. After the interbody fusion procedures, percutaneous pedicles screw fixation was performed. Biportal endoscopic TLIF achieved complete neural decompression through laminectomy and facetectomy like conventional TLIF. Endplate preparation was performed completely under a clear and magnified endoscopic view. It was also feasible to insert a large TLIF cage or 2 cages for PLIF without exiting nerve root injury. Biportal endoscopic TLIF might have the advantages of endoscopic surgery as well as minimally invasive fusion surgery. Direct neural decompression, endplate preparation under endoscopic guidance, and the insertion of a large TLIF cage or 2 PLIF cages may be the merits of biportal endoscopic lumbar fusion procedures.